2019
DOI: 10.1158/0008-5472.can-19-0458
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Hallmarks of Metastasis

Abstract: Metastasis is the primary cause of cancer morbidity and mortality. The process involves a complex interplay between intrinsic tumor cell properties as well as interactions between cancer cells and multiple microenvironments. The outcome is the development of a nearby or distant discontiguous secondary mass. To successfully disseminate, metastatic cells acquire properties in addition to those necessary to become neoplastic. Heterogeneity in mechanisms involved, routes of dissemination, redundancy of molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
463
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(479 citation statements)
references
References 249 publications
(265 reference statements)
1
463
0
15
Order By: Relevance
“…We propose that CCM1 is an important regulator of the YAP/TAZ and AR signaling in PCa cells. That stated, our evidence indicates that despite the concomitant activation of multiple pro-tumoral signaling pathways, suppression of CCM1 ameliorated representative metastatic hallmarks, namely motility, invasion and survival (43), in multiple types of both androgen-responsive and androgen-non-responsive metastatic PCa cells. CCM1 may not be sufficient to induce tumorigenesis, but it appears to unleash the oncogenic potential of multiple cellular signals, promoting cancer progression including the invasiveness Based on genetic aberrations of AR or the increased synthesis of androgens (in the tumor microenvironment [TME]) or adrenal androgen precursors, it has been reported that AR expression is increased (44) and that AR signaling is consistent with the castration level of androgens in patients with mCRPC.…”
Section: Discussionmentioning
confidence: 62%
“…We propose that CCM1 is an important regulator of the YAP/TAZ and AR signaling in PCa cells. That stated, our evidence indicates that despite the concomitant activation of multiple pro-tumoral signaling pathways, suppression of CCM1 ameliorated representative metastatic hallmarks, namely motility, invasion and survival (43), in multiple types of both androgen-responsive and androgen-non-responsive metastatic PCa cells. CCM1 may not be sufficient to induce tumorigenesis, but it appears to unleash the oncogenic potential of multiple cellular signals, promoting cancer progression including the invasiveness Based on genetic aberrations of AR or the increased synthesis of androgens (in the tumor microenvironment [TME]) or adrenal androgen precursors, it has been reported that AR expression is increased (44) and that AR signaling is consistent with the castration level of androgens in patients with mCRPC.…”
Section: Discussionmentioning
confidence: 62%
“…Recent results extend the risk for metastasis to 10 years postpartum, which makes the percentage of young breast cancer patients who are considered postpartum and as such at high risk for metastasis nearly 50%(26). A recent publication by Welch and Hurst defines the hallmarks of metastasis as motility and invasion, modulation of the microenvironment, plasticity and colonization(27). Here, using pre-clinical models, we identify potential tumor intrinsic and extrinsic roles for SEMA7A in promotion of PPBC growth including invasion, modulation of the microenvironment, survival in hostile environments such as the circulation, and colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is thought to be the ultimate manifestation of a neoplastic cell's evolution towards becoming autonomous from the host, and remains the main cause of cancer-related death 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cure of most cancers is probable whenever diagnosis occurs before cells have spread beyond the tissue of origin; otherwise, cancer is often referred to as incurable [33][34][35] . According to Welch and Hurst 28 , the four hallmarks of metastasis are motility and invasion, modulate microenvironment, plasticity and colonization. Regarding mechanisms of HIF-mediated metastasis, hypoxia and activation of HIF signaling influence multiple steps within the metastatic cascade, including invasion and migration, intravasation and extravasation, and establishment of the premetastatic niche, as well as survival and growth at the distant site 24,36,37 .…”
Section: Introductionmentioning
confidence: 99%